Elderly Outcomes After Hospitalization: The Hospital Frailty Risk Score Applied on the French Health Data Hub. (June 2023) - Dubnitskiy-Robin, Sophie; Laurent, Emeline; Herbert, Julien; Fougère, Bertrand; Guillon-Grammatico, Leslie
Objectives: To demonstrate the association between the Hospital Frailty Risk Score (HFRS) and 30-day mortality, 30-day hospital readmission and length of stay (LOS) in France.Methods: Logistic regressions were performed using data recorded in the French national health data system ( SNDS) for elderly patients (≥75 years old) hospitalized in France in 2017.Results: Over the 1, 111, 090 patients included, 30-day mortality was associated with the HFRS: adjusted OR (aOR) for an intermediate HFRS (5–15 points) was 1.91 [95% confidence interval (95% IC); 1.87–1.95] and aOR 2.57 [95% IC; 2.50–2.64] for high HFRS (>15 points), as compared to low HFRS (<5 points). LOS >10 days increased with the HFRS (aOR = 1.36 [95% IC; 1.34–1.38] for an intermediate HFRS and aOR 1.51 [95% IC; 1.48–1.54] for a high HFRS). A high HFRS was associated with 30-day hospital readmission (aOR = 1.06 [95% IC; 1.04–1.08]).Discussion: This real-life analysis of in- and out-patient healthcare pathways confirmed the HFRS's ability to predict adverse outcomes, after adjustment on social deprivation.